Clinicopathological features and prognosis of colonic and rectal gastrointestinal stromal tumors: A propensity score matching analysis - Li, Chen; Lu, Yunwei; Zhang, Meng-meng; Wu, Hao; Li, Han; Ye, Ying-Jiang; Jiang, Kewei (Frontiers in Surgery, 2022)
Background Colonic gastrointestinal stromal tumor (cGIST) and rectal gastrointestinal stromal tumor (rGIST) are two rare subtypes of gastrointestinal stromal tumor (GIST). The view that colonic and rectal carcinoma are different is generally accepted; however, whether there is a difference between cGIST and rGIST is still unknown. Here, we aimed to provide evidence for future clinical management and research by comparing the differences between the two types of GIST in the above-mentioned aspects. Methods Patients were enrolled from three medical centers in China and published literature was collected following the inclusion and exclusion criteria. Propensity score matching was used to eliminate differences between cohorts. Results Between cGIST and rGIST patients, significant differences were observed in age, tumor size, mitotic index, NIH risk category, growth pattern, and symptoms. Adjuvant therapy is used in a high proportion of cGIST patients, and neoadjuvant therapy is used in a high proportion of rGIST patients. Although local resection is the main surgical method in both cohorts, the proportion is higher in cGIST patients. The overall survival of rGIST patients was better than that of the cGIST patients before propensity score matching (PSM). Interestingly, no significant differences in prognosis were observed after PSM. Conclusions Although there were significant differences between cGIST and rGIST patients in baseline characteristics, clinicopathological features, treatment choice, and overall survival rate before PSM, no significant differences in long-term survival were observed between the two groups after PSM. In our study, there may be no differences in the tumor entity between cGIST and rGIST.